2007
DOI: 10.1038/sj.embor.7401063
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying mutually exclusive expression of virulence genes by malaria parasites

Abstract: A fundamental yet poorly understood aspect of gene regulation in eukaryotic organisms is the mechanisms that control allelic exclusion and mutually exclusive gene expression. In the malaria parasite Plasmodium falciparum, this process regulates expression of the var gene family-a large, hypervariable repertoire of genes that are responsible for the ability of the parasite to evade the host immune system and for pathogenesis of the disease. A central problem in understanding this process concerns the mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
161
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 116 publications
(169 citation statements)
references
References 21 publications
8
161
0
Order By: Relevance
“…Furthermore, changes in subnuclear localization have been observed to be associated with var gene activation (Duraisingh et al 2005;Ralph et al 2005b;Dzikowski et al 2007), which has led to the hypothesis of a defined var subnuclear transcription site.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, changes in subnuclear localization have been observed to be associated with var gene activation (Duraisingh et al 2005;Ralph et al 2005b;Dzikowski et al 2007), which has led to the hypothesis of a defined var subnuclear transcription site.…”
Section: Introductionmentioning
confidence: 99%
“…The details of the mechanism maintaining var gene silencing are largely unknown; however, recent work indicates that each var gene is regulated by two separate promoters, one upstream of the coding region and a second within the relatively conserved intron (Calderwood et al 2003;Dzikowski et al 2007). The upstream promoter from the single expressed gene produces var mRNA and is active in the ring stages of the cell cycle (8-20 h after invasion), while the intron promoter produces a noncoding RNA and is active in pigmented trophozoite and schizont stages (24-48 h after invasion) (Kyes et al 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The promoter located upstream of exon 1 drives the expression of the var gene, which is subject to mutually exclusive expression regulation and hence only one is active at any time, while the promoter located within the intron appears to be active in most if not all var genes (Epp et al 2009). Studies have shown that proper silencing of the var gene relies on the intron promoter activity, the pairing of the upstream and intron promoters, and passing through at least one cell cycle (Calderwood et al 2003;Deitsch et al 2001;Dzikowski et al 2007;Frank et al 2006). The detailed mechanism underlying the regulatory role of the intron promoter is still unknown.…”
Section: Sir2-mediated Tpe Plays An Essential Role In Manoallelic Expmentioning
confidence: 99%
“…Fluorescent in situ hybridization FISH was carried out as described by Dzikowski et al (2007), with the exceptions that the prawn sample was prepared according to Justo et al (1991) and that the probe used was the PCR probe of nucleotides 1-2003 of the B3 kbp fragment identified (primers available upon request). Samples were prepared from several male and female gonads, and the signal was scored for a total of 74 nuclei that could be distinguished morphologically.…”
Section: Genome Walkingmentioning
confidence: 99%